Guías de laboratorio experimental para la enseñanza de Mecánica Clásica dirigido a estudiantes de la Carrera de Pedagogía de las Ciencias Experimentales: Matemáticas y la Física - Pilco Sucuy, Jessica Alexandra (2024)
The effective teaching of Classical Mechanics constitutes a fundamental pillar in the formation of physics students. Despite the availability of didactic resources, there is a significant lack of experimental laboratory guides adapted to the specific needs of students. Therefore, the present research work aims to propose experimental laboratory guides for the teaching of Classical Mechanics in students of the Pedagogy of Experimental Sciences: Mathematics and Physics of the National University of Chimborazo for the strengthening of competences in the subjects of Particle Mechanics and Particle Dynamics. The research has a quantitative approach of transversal and descriptive type, with a non-experimental design, the sample was selected with a non-probabilistic sampling of intentional type, corresponding to students of second, third and fourth semester of the aforementioned major. As an instrument for data collection, a questionnaire was applied in order to know the students' attitudes towards the use of experimental practices. From the results obtained, it is shown that the attitude of the students under study towards the use of laboratory practices is positive, recognizing the importance towards the development of practical skills, and a high interest in having a repository of experimental laboratory guides. Finally, as a proposal, experimental laboratory guides were elaborated and validated, using the laboratory equipment of the Faculty of Education Sciences of the National University of Chimborazo, for the following topics: the basic principles of Physics, one-dimensional and two-dimensional motion, as well as Newton's laws of motion and their applications.